Un œil nouveauLe Ralenti scientifique à la construction de l’avant-garde (Cinéma & Cie. Film and Media Studies Journal, 2018)
A long-standing and intimate link exists between avant-garde and scientific cinema. In the 1920s, in fact, the former contributed to the construction of the latter: on the one hand, by its systematic inclusion in film clubs and film societies screening programs; and on the other, by catalyzing the theoretical reflection on medium specificity because of the particular techniques it develops. In this essay I will examine the contribution of scientific slow motion to 1920s film theory, investigating how this technique conveys an epistemological shift in the concept of revelation, from the scientific observation of the invisible to the naked eye, to the deep understanding of previously unknown aspects of reality. Through the words of scholars and philosophers, as well as filmmakers and theorists (Louis Delluc, Germaine Dulac, Jean Epstein and Jean Tedesco, among others), I will discuss several concepts that marked the aesthetic theories of the time, such as photogénie, cinéma pur, and optical unconscious.